The Practice of State Ideological Apparatuses in Matthew Pearl's the Dante Club - Rizal Octofianto Datau (English Department FKIP Universitas Muhammadiyah Surabaya Indonesia, 2015)
The Dante Club is an American historical fiction written by Matthew Pearl. The story takes place in the state of Massachusetts during the aftermath of the American Civil War. The two major issues presented in the novel are xenophobia and anti-Catholicism. Specifically, it tells about a controversy over the Italian literary work, “Divine Comedy”, which is being translated into English by a group of notable poets named Dante Club. Their endeavor is considered as promoting Catholicism which is subjectively interpreted as an act of threatening the state. Based on Louis Althusser’s theoretical perspective, the work of the state authorities to hinder the group’s effort is seen as the manifestation of ideological practice. The theory points out that such an interference may commonly be found to be performed by two types of powerful institution, namely Ideological State Apparatuses (ISAs) and Repressive State Apparatuses (RSAs).This study discusses the practice of state ideology which is intended to maintain the state power as described in the novel. The focus is on answering the question of how ISAs and RSAs are authorized to exert their role to control people as well as to influence them on behalf of the state.